Tear it down now - Bowes, E. Nelson (The Appraisal journal, 2017)
The author of Obsolescence, David M. Abramson, is an associate professor of art history and director of architectural studies at Tufts University. "What middle-class evaluators quantified as obsolete-crowded, noisy tenements and roads, mixed with stores and taverns, children playing in the streets-were for the West Enders themselves good places to play, socialize, and communicate, reinforcing ties of kinship and community." (page 51) There is a lot of content in this chapter that was new to me. The book quotes Peter Blake, editor of Architectural Forum, who blamed the 1954 tax code's accelerated depreciation rate, which was meant to encourage development with a quick write-off, but "all of a sudden an owner was rewarded for selling out fast!" (page 110) To give a sense of the times, Abramson offers quotes from the post-war growth era, such as "Yesterday's house is as obsolete as yesterday's car" (page 66, from year 1959); article titles such as "Expendability: Towards Throwaway Architecture" (page 71, from year 1963); and publication titles such as Kinetic Architecture (page 76, from mid-1960s), all of which demonstrate the new obsolescence thinking. Building features, such as open space and movable walls, were tried (successfully in some cases) to solve the challenge of functional obsolescence by allowing the function to change without removing the building. The text examples (pages 118-121) suggest that this style was adopted more often for public structures, which are not subject to obsolescence in the original economic sense or in terms of market demand. [...]there are no predictions...